Pengaruh Inovasi Kelembagaan Pada Pengembangan Klaster Batik Laweyan Kota Surakarta - Ery Dyah Wulandari (Department of Urban and Regional Planning, Diponegoro University, 2013)
Klaster Batik Laweyan is one of the cluster experienced significant growth as indicated by the existence of institutional innovations in it. This is evident from the condition of the business in the previous Laweyan dim currently being developed due to the formation Forum Pengembangan Kampoeng Batik Laweyan the container in cluster development. This study raises the question